O estágio curricular supervisionado em Educação Física e o processo de profissionalização do ensino: um estudo de casos múltiplos - Ananias, Elisângela Venancio [UNESP] (2016)
The research had at its core the Physical Education Teacher Education based on the reading and analysis of the supervised curricular traineeship programs mainly focused in three contexts. The objectives were: a) understand the influences of the professionalization movement in teacher education by three traineeship proposals in Portugal, United States and Brazil; b) identify and analyze the constitution of the three teacher education programs; c) know and analyze the three traineeship proposals in each context ; d) verify the influence of the professionalization movement in these three traineeship proposals. It is a qualitative research in the form of multiple cases that were composed by Towson University, USA, Instituto Superior da Maia, Portugal, and the the University of São Paulo State, Rio Claro, Brazil. The informants were: three coordinators of the teacher education programs, three supervisors, four menthor teachers, and five teacher candidates, all being from the different contexts. Document analysis, non-systematic observation, and semi-structured interview on the spot were used as data-collecting instruments. For the data analysis, the steps provided within the study of multiple cases, and the software NVIVO were utilized as resources. Thus, the research presented as a result the composition of three cases through which it was possible to discuss the nuances of the professionalization process, and the relationship between the teacher education traineeship programs and a degree in Physical Education. The three studied programs were reformed preceding from the idea of professionalization advocated by the United States based on reports from the 1980s. Regarding the training programs, including supervised traineeship, it was verified that they are predominantly organized and conducted by higher education teachers. Therefore, it is necessary to contextualize the reality of schools so that the teaching practice is more efficient in supporting the gradual inclusion of future educators in primary and secondary education. In this regard, the urgent need for collaborative work between schools and universities was reinforced. Also, advances were made with respect to the comprehension of the weight of sociocultural factors of each case, which need to be preserved. Through such factors, the establishment of dialogues with other realities is possible, envisioning the promotion of strategies, and legitimate decisions in face of challenges that emerge from contemporaneity – producing permanent access to those who exert the teaching profession on a daily basis.